2009
DOI: 10.1002/qj.407
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for non‐uniform static stability in orographic drag parametrization

Abstract: ABSTRACT:The extent to which the drag due to flow blocking by mountains is affected by height variations in the static stability is examined using a series of numerical simulations. The results are used to investigate how best to estimate the depth-averaged upwind static stability for the purposes of parametrizing the drag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Allaerts and Meyers [15,21] showed that the upward displacement of the boundary layer by flow deceleration in the wind farm excites gravity waves, supporting the suggestion from Smith [49]. Reinecke and Durran [50], and Vosper et al [51] demonstrated that a Froude number could be used to characterize the blocking behavior of flow over mountains and the onset of upwind mountain stagnation. Using a similar approach, the Froude number:…”
Section: Wind Farm Induction Regionsupporting
confidence: 50%
See 1 more Smart Citation
“…Allaerts and Meyers [15,21] showed that the upward displacement of the boundary layer by flow deceleration in the wind farm excites gravity waves, supporting the suggestion from Smith [49]. Reinecke and Durran [50], and Vosper et al [51] demonstrated that a Froude number could be used to characterize the blocking behavior of flow over mountains and the onset of upwind mountain stagnation. Using a similar approach, the Froude number:…”
Section: Wind Farm Induction Regionsupporting
confidence: 50%
“…is the reduced gravity taking into account the stability variation between the ground and a depth scale D h , and z i is the height above which the stability is independent of height and is prescribed with a fixed Γ. Vosper et al [51] demonstrated that the thermal stability over a mountain has a significant effect on the gravity-wave-induced flow blockage, and the depth scale D h = z i + U N could account for such stability effect on mountain flows. The Fr of a flow is the ratio of the flow speed to the speed of the induced gravity waves.…”
Section: Wind Farm Induction Regionmentioning
confidence: 99%
“…Changes in the atmospheric component between the HadGEM2 and HadGEM3 model families include the ENDGame dynamical core (Wood et al, 2014), the inclusion of a prognostic cloud and condensate scheme (PC2; Wilson et al, 2008), increased convective entrainment and detrainment, a new orographic gravity wave drag (GWD) representation (Vosper et al, 2009), and numerous other changes (see Walters et al, 2011Walters et al, , 2014Walters et al, , 2017. In addition, the vertical resolution has been increased and the model lid extended from 40 to 85 km.…”
Section: Hadgemmentioning
confidence: 99%
“…We use the MetUM Global Atmosphere version 6.0 (MetUM-GA6; Walters et al, 2016;Williams et al, 2015), which is an updated version of the MetUM-GA3 (Walters et al, 2011) configuration analysed by Klingaman et al (2017), with a different dynamical core (ENDGAME; Wood et al, 2014 orographic gravity-wave drag representation (Vosper et al, 2009), and several changes to the convective parametrization (see Walters et al (2011Walters et al ( , 2016 for details). MetUM-GA6 includes a 25 % increase to the rates of mixing entrainment and detrainment for diagnosed deep convection relative to MetUM-GA3, implemented to improve the representation of tropical sub-seasonal variability following Klingaman and Woolnough (2014).…”
Section: Model Descriptionmentioning
confidence: 99%